Voriconazole increases the risk for cutaneous squamous cell carcinoma after lung transplantation. (24th October 2016) - Kolaitis, Nicholas A.; Duffy, Erin; Zhang, Alice; Lo, Michelle; Barba, David T.; Chen, Meng; Soriano, Teresa; Hu, Jenny; Nabili, Vishad; Saggar, Rajeev; Sayah, David M.; DerHovanessian, Ariss; et al.
Summary: Lung transplant recipients (LTR) are at high risk of cutaneous squamous cell carcinoma (SCC). Voriconazole exposure after lung transplant has recently been reported as a risk factor for SCC. We sought to study the relationship between fungal prophylaxis with voriconazole and the risk of SCC in sequential cohorts from a single center. We evaluated 400 adult LTR at UCLA between 7/1/2005 and 12/22/2012. On 7/1/2009, our center instituted a protocol switch from targeted to universal antifungal prophylaxis for at least 6 months post‐transplant. Using Cox proportional hazards models, time to SCC was compared between targeted ( N = 199) and universal ( N = 201) prophylaxis cohorts. Cox models were also used to assess SCC risk as a function of time‐dependent cumulative exposure to voriconazole and other antifungal agents. The risk of SCC was greater in the universal prophylaxis cohort (HR 2.02, P < 0.01). Voriconazole exposure was greater in the universal prophylaxis cohort, and the cumulative exposure to voriconazole was associated with SCC (HR 1.75, P < 0.01), even after adjustment for other important SCC risk factors. Voriconazole did not increase the risk of advanced tumors. Exposure to other antifungal agents was not associated with SCC. Voriconazole should be used cautiously in this population.